Rebuilding sustainable communities for children and their families after disasters : a global survey - Awotona, Adenrele A. (Cambridge Scholars, 2010)
Disasters impose enormous misery on children, the most vulnerable members of the community. Records show that two million children have died as a direct consequence of armed conflict over the past decade. Globally, millions more have suffered death, disease, and dislocation as a result of such natural disasters as earthquakes, droughts, and floods. And even when emergency relief is available, permanent human damage remains; all too often, families fall apart, women are assaulted and degraded ...